ANALISIS KOMPONEN UTAMA PADA DINAS KETENAGAKERJAAN BAGIAN PENEMPATAN DAN PERLUASAN KERJA MENCARI PEKERJAAN MENURUT GOLONGAN PEKERJAAN - Muliady Faisal; Syalam Ali Wira Dinata; Dewi Ratna Sari (Journal of Innovation Research and Knowledge, 2023)
Job seekers are a process that matches jobs to match. If all workers and all types of workers are the same, then all workers are suitable for all types of work, then job search will not be a problem. In this research, an analysis is needed to determine the job seeker who chooses according to the desired job group. By using the analysis of the Pricipal Component Analysis using SPSS, the output is the value of KMO and Barlett's Test, MSA, communality, Total Variance, Scree plot and Matrix Components. By using the Main Component Analysis methodology to reduce/reduce the factors that affect job seekers according to groups from 9 existing variables, the results of the reduction are obtained.